International Oil Price and RMB Real Exchange Rate - Pan, Dong (2012)
This paper aims to test whether there are relationships between the real exchange rate and crude oil price in China by using the monthly time series data from 1994m1 to 2005m7. Cointegration test following by Granger causality test and Vector Error Correction model have been used to analyse both the long run and short run dynamics. The results show that the relationship between RMB real exchange rate and crude oil price is positive in the short run. However, in the long run, before China’s exchange rate regime has changed, the increase of oil price would cause appreciation of RMB real exchange rate. After China switch to a more flexible exchange rate than before, the rise of oil price may lead to depreciation of its exchange rate which means the RMB is appreciated. Moreover, only the oil price Granger cause real exchange rate, but not vice versa.